The Influence of Trust Level and Consumer Behavior on Shopee-Pay Electronic Payment Customer Satisfaction - Putri, Zahra; Syila Andita; Nuril Sasmito (Journal of Current Research In Multidisciplinary, 2023)
This research aims to determine the influence of consumer behavior on the level of customer trust. This research uses a quantitative method with a descriptive approach. Researchers will collect data from various sources. The research that will be carried out to test is research in the form of answers to questions given to pupils, students, and workers. Through this research, it is hoped that it can provide accurate information and data according to the facts that occur in the field. Questionnaires or surveys will later be distributed, containing the necessary explanations regarding this research. The data obtained will later be in the form of respondents' responses regarding the ease of ShopeePay electronic payments on customer satisfaction. The population in this research is ShopeePay users with an age range of 17 to 40 years. The data obtained is primary data obtained from distributing questionnaires to respondents. From the results of the research and analysis carried out, it was concluded that perceived consumer behavior factors and perceived levels of trust can influence customer satisfaction when making electronic payments using ShopeePay. This was proven through validity tests of perceived convenience, perceived trust, and consumer behavior, all of which passed and were declared valid functional value variables.